Grouting Mechanism of Cement-Based Slurry in a Concentric Annulus under High Groundwater Pressure - Weijie Zhang; Chenghao Han; Lianzhen Zhang; Jiuchuan Wei; Huiyong Yin; Weiwei Han; Chao Xie; Wenwu Zhou (Advances in Civil Engineering)
The flow of cement-based slurry within concentric annular geometry is a major problem of study in the field of engineering, especially regarding the prevention of water ingress in an annulus formed during shaft construction utilizing the artificial freezing technique in China. In this study, an analytical governing equation of motion for the axial flow of an incompressible Newtonian fluid in a long concentric annulus is derived under the condition of high groundwater pressure. A stepwise calculation method is proposed to describe the grouting process based on two injection modes, namely, flow rate control and pressure control. The injection time is divided into a series of time segments; correspondingly, the grouted zone is subdivided into infinitesimal elements. Some key parameters, such as the location, dimension, slurry viscosity, and pressure gradient of each element, can be obtained using the developed MATLAB program. On this basis, the distribution of pressure and slurry viscosity in the grouted zone and the variations in injection pressure at the grouting point and grouting flow rate are determined. Two injection mode cases are investigated to reveal the grout propagation in the concentric annulus. Finally, numerical simulations are conducted and employed to validate and calibrate the calculated results. The results obtained by the present stepwise calculation method show good agreement with the numerical results.